PRODUCT KNOWLEDGE DAN PRODUCT PROMOTION TERHADAP PURCHASE SATISFACTION DAN REPURCHASE INTENTION SELAMA PANDEMIC COVID-19 - Kholifah Kholifah (Journal of Digital Business and Management, 2022)
The Covid-19 pandemic has fundamentally changed the world. The pandemic is forcing consumers to change their buying attitudes and habits (Blackburn, 2020). Recent studies have begun to focus more on the market perspective by investigating consumer vulnerability from the perspectives of poverty and low incomes (Glavas et al., 2020), decision making (Choudhury et al., 2019; Hill & Sharma, 2020), and markets (Stewart & Yap. , 2020). This study aims to explain this aspect. This research is a quantitative research and the respondents in this research are 100. In this study, the sample was taken by non-probability sampling, namely by using the accidental sampling technique. Based on data analysis, it is known: H1 is accepted, there is an effect of Product Knowledge on Purchase Satisfaction, H2 is accepted: there is an effect of Product Knowledge on repurchase intention, H3 is accepted: there is an effect of Product Promotion on Purchase Satisfaction, H4 is accepted: there is an effect of Product Promotion on Repurchase Intention and H5 is accepted. : there is an influence between Purchase Satisfaction on repurchase intention. Keywords: product knowledge, product promotion, Purchase Satisfaction, repurchase intention